2010
DOI: 10.4236/health.2010.25076
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic activity of Phyllanthus niruri (Linn.) in rats

Abstract: Aqueous extract of Phyllanthus niruri (200 mg/kg and 400 mg/kg. p.o. single dose) was tested for its diuretic activity and compared with the standard drug hydrochlorothiazide (10 mg/ kg p.o.; single dose). Significant increase in the volume of urine and excretion of sodium, potassium and chloride was recorded when aqueous extract of Phyllanthus niruri was administered to hydrated albino rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This might be due to the inherent antioxidant and free-radical-scavenging principle(s) in the extract (Adeneye et al, 2008). Aqueous extract of P. niruri has significant diuretic activity, and it has significantly increased the excretion of sodium, potassium, and chloride as compared to that of the control (Udupa et al, 2010). In the present study, the histological examination revealed minimal damage to the brain, liver, and kidney in animals that received P. amarus after the termination of arsenic in the current study, it is evident that P. amarus can cause regeneration of tissues caused by arsenic.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the inherent antioxidant and free-radical-scavenging principle(s) in the extract (Adeneye et al, 2008). Aqueous extract of P. niruri has significant diuretic activity, and it has significantly increased the excretion of sodium, potassium, and chloride as compared to that of the control (Udupa et al, 2010). In the present study, the histological examination revealed minimal damage to the brain, liver, and kidney in animals that received P. amarus after the termination of arsenic in the current study, it is evident that P. amarus can cause regeneration of tissues caused by arsenic.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the patients were aware of the importance of fluid intake to prevent the formation of new calculi and were thus already consuming the quantity of liquid recommended at the beginning of the study; this would have resulted in no significant change in urine volume. The diuretic effects of P. niruri have been described in experimental studies ( 10 , 15 ), though Nishiura et al ( 11 ) reported different results in a clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Chrysanthellum americanum in the management of urinary stones is due to its interference, through the chrysantellin, a saponin, with some stages of crystallization in urine, such as a reduction in the nucleation, growth and aggregation of calcium oxalate crystals (8). Moreover, the synergistic effect of Phyllanthus niruri and Chrysanthellum americanum is probably due to its diuretic effects (12,13). Furthermore, this food supplement contains potassium and magnesium citrates, although previous studies did not favor potassium citrate therapy.…”
Section: Role Of Phytotherapy In the Management Of Urinary Stones And Mechanism Of Actionmentioning
confidence: 99%